Rapid Centrifugation in the Routine Hemostasis Laboratory - Wolfensberger, Nathan; Georgiou, Georgios; Giabbani, Evelyne; Reusser, Marianne; Njue, Linet M.; Fiedler, Martin; Leichtle, Alexander B.; Nagler, Michael (Thrombosis and Haemostasis, 2019)
Background The use of short and uniform centrifugation schemes contributes significantly to the successful automation of laboratory procedures. It is however unclear if this is applicable to the hemostasis laboratory.Objectives This article assesses the accuracy of measurements obtained with a rapid, high-speed centrifugation scheme in a large set of hemostasis tests, covering the full spectrum of values obtained in clinical practice, and using meaningful statistical measures.Methods Two citrated plasma samples were obtained from consecutive patients of a tertiary hospital with suspected abnormal hemostasis tests and processed with two centrifugation schemes in parallel: 1,500 × g for 10 minutes and 3,137 × g for 7 minutes. The following tests were conducted: prothrombin time (n = 125), international normalized ratio (n = 146), activated partial thromboplastin time (n = 119), thrombin time (n = 105), fibrinogen (n = 125), factor (F)II (n = 69), FV (n = 64), FVII (n = 64), FX (n = 67), FVIII (n = 55), FIX (n = 37), FXI (n = 35), and FXIII (n = 20), D-dimer (n = 34), antithrombin (n = 31), anti-Xa activity (n = 30), von Willebrand antigen (n = 25), and von Willebrand activity (VWF:GPIbM; n = 27).Results A wide range of results were obtained in all tests. Spearman's rank correlation coefficient was at least 0.95 for all tests except FV, FIX, and FXI. The coverage probability π at a given deviation index κ of 15% was above 0.9 for all tests except FV, FVII, FX, FVIII, FIX, FXI, and VWF:GPIbM, suggesting a lack of agreement.Conclusion Our results suggest that high-speed centrifugation is applicable to the majority of routine hemostasis parameters. The coverage probability was more sensitive than Spearman's rank correlation to detect disagreement among centrifugation schemes.
Keywords: centrifugation; automation; laboratory/instrumentation; laboratory/methods; laboratory/standards; blood coagulation tests